Utilization Of The Opexams Website As An Educational Instructional Media In Teaching Arabic Reading Skills/ Pemanfaatan Website Opexams Sebagai Media Instruksional Edukatif Dalam Pembelajaran Maharah Qiraah - Nuruddin, Dzaky; Mufidah, Nuril (Jurnal Bahasa Arab, 2025)
This study describes the use of the Opexams website, its development, and its use as an instructional medium in learning reading skills. Data collection techniques used documentation from various relevant sources, such as research results, books, and articles. Data analysis used the Logical Framework Approach model. The results of the study indicate that using the Opexams website can help students learn Arabic reading skills by utilizing various features and services provided. These features help improve reading skills, develop students' abstract thinking skills, and create learning media. The Opexams website provides broad accessibility and an interactive nature, supporting learning. Features such as Quizzes, Question Bank, Online Exams, and AI Question Generator offer students a diverse and attractive learning experience.